Identification and intercomparison of surface‐based inversions over Antarctica from IASI, ERA‐Interim, and Concordiasi dropsonde data. Issue 15 (13th August 2016) - Boylan, Patrick; Wang, Junhong; Cohn, Stephen A.; Hultberg, Tim; August, Thomas
Abstract: Surface‐based temperature inversions (SBIs) occur frequently over Antarctica and play an important role in climate and weather. Antarctic SBIs are examined during the austral spring of 2010 using measurements from dropsondes, ERA‐Interim Atmospheric Reanalysis Model, and the recently released version 6 of the Infrared Atmospheric Sounding Interferometer (IASI) level 2 product. A SBI detection algorithm is applied to temperature profiles from these data sets. The results will be used to determine if satellite and reanalysis products can accurately characterize SBIs, and if so, then they may be used to study SBIs outside of the spring 2010 study period. From the dropsonde data, SBIs occur in 20% of profiles over sea ice and 54% of profiles over land. IASI and ERA‐Interim surface air temperatures are found to be significantly warmer than dropsonde observations at high plateau regions, while IASI surface air temperatures are colder over sea ice. IASI and ERA‐Interim have a cold bias at nearly all levels above the surface when compared to the dropsonde. SBIs are characterized by their frequency, depth, and intensity. It is found that SBIs are more prevalent, deeper, and more intense over the continent than over sea ice, especially at higher surface elevations. Using IASI and ERA‐Interim data the detection algorithm has a high probability of detection of SBIs but is found to severely overestimate the depth and underestimate the intensity for both data sets. These overestimation and underestimation are primarily due to the existence of extremely shallow inversion layers that neither satellite nor reanalysis products can resolve. Key Points: Satellite and reanalysis data tend to overestimate SBI depth and underestimate SBI intensity IR satellite and reanalysis products found to have cold temperature bias in lower troposphere Surface air temperature agreement is dependent on surface elevation and surface type